2013
DOI: 10.1186/1472-6963-13-394
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurse working hours on patient safety culture: a cross-national survey including Japan, the United States and Chinese Taiwan using the Hospital Survey on Patient Safety Culture

Abstract: BackgroundA positive patient safety culture (PSC) is one of the most critical components to improve healthcare quality and safety. The Hospital Survey on Patient Safety Culture (HSOPS), developed by the US Agency for Healthcare Research and Quality, has been used to assess PSC in 31 countries. However, little is known about the impact of nurse working hours on PSC. We hypothesized that long nurse working hours would deteriorate PSC, and that the deterioration patterns would vary between countries. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 17 publications
2
63
0
1
Order By: Relevance
“…We found nurses who worked 35 h weekly were more positive towards safety culture than those worked >35 h. A study conducted by Wu et al. () found that longer working hours were associated with low patient safety grade, and Rogers et al. () reported a 3.29 times increased chance of making an error among nurses who worked for a longer duration (>12.5 h shift in 24‐h period).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found nurses who worked 35 h weekly were more positive towards safety culture than those worked >35 h. A study conducted by Wu et al. () found that longer working hours were associated with low patient safety grade, and Rogers et al. () reported a 3.29 times increased chance of making an error among nurses who worked for a longer duration (>12.5 h shift in 24‐h period).…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, at least one nurse has to work with a volunteer nurse on evening and night shift duty together (17 consecutive hours). We found nurses who worked 35 h weekly were more positive towards safety culture than those worked >35 h. A study conducted by Wu et al (2013) found that longer working hours were associated with low patient safety grade, and Rogers et al (2004) reported a 3.29 times increased chance of making an error among nurses who worked for a longer duration (>12.5 h shift in 24-h period). In contrast, an increasing number of reporting errors could be a sign of positive patient safety culture when staff work in an organization characterized by a blame-free environment and feel free to speak up and report errors.…”
Section: Discussionmentioning
confidence: 64%
“…Hospital management must have a central role in developing safety culture at the system level within hospitals to ensure that nurses caring for patients do so safely (34). Previous studies have revealed that patient safety scores have deteriorated and that the number of reported events increases with longer working hours (35,36). Therefore, managers should decrease long working hours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that working extended hours can lead to missed nursing care and medical errors, which in turn negatively impact patient safety and the quality of patient care (Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014;Reed, 2013;Rogers, Hwang, Scott, Aiken, & Dinges, 2004;Wu et al, 2013). Working many hours per week might subject nurses to fatigue and render them unable to perform all necessary nursing care activities.…”
Section: Discussionmentioning
confidence: 99%
“…Working many hours per week might subject nurses to fatigue and render them unable to perform all necessary nursing care activities. Previous research has shown that working extended hours can lead to missed nursing care and medical errors, which in turn negatively impact patient safety and the quality of patient care (Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014;Reed, 2013;Rogers, Hwang, Scott, Aiken, & Dinges, 2004;Wu et al, 2013). For instance, a study conducted in Hong Kong on the effect of workload on the survival of critical patients found that a patient was less likely to survive to hospital discharge if they were cared for by a nurse working greater than 52 hours per week.…”
Section: Discussionmentioning
confidence: 99%